Correlation and Path Analysis in Different Wheat Genotypes for Grain Yield and its Related Traits: Wheat Genotypes for Grain Yield - Shazadi Mahpara; Muhammad Imran; Muhammad Arslan Khalid; Nida Fatima; Ali Ammar; Shoaib Liaqat; Sadia Kanwal (Biological Sciences - PJSIR, 2024)
Wheat (Triticum aestivum L.) is one of the most important cereal crops and is grown all around the world after rice and maize. Wheat plays a vital role in human and animal nutrition because it is a major source of carbohydrates. Wheat is facing different problems like climate change, biotic and abiotic stress. The research was conducted to study heritability and interrelationship among grain yield and its components in different wheat genotypes. The experimental material was composed of 20 genotypes of wheat with three replications. The present study was laid out in the field of the Department of Plant Breeding and Genetics, Ghazi University, Dera Ghazi Khan. At maturity, grain yield and its related traits were observed. Analysis of variance was analyzed using Statistix 8.1 Software. Results for ANOVA showed that all genotypes showed a highly significant effect among all the characters, while phenotypic and genotypic correlations showed that plant height had significant correlations with grain yield and days to maturity had a negatively highly significant effect on grain yield per plant. Path coefficient analysis revealed that the direct effect of flag leaf area, plant height, spike length, spikelets per spike, and grain weight per spike on grain yield was observed as positive. All other traits showed negative direct affect values. The indirect effect of flag leaf area and number of grains per spike was observed as positive for grain yield per plant. Results showed that genotype F2 had a maximum value for flag leaf area and days to maturity. Genotype AAS 2011 had the highest values for the number of tillers per plant and number of spikelets per plant than other varieties. Genotype A14 had maximum values for yield per plant.